P‐Wave Duration Is Associated With Aging Patterns in Structural Brain Networks - Elizabeth Haddad; William Matloff; Gilsoon Park; Mengting Liu; Neda Jahanshad; Ho Sung Kim (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Impaired cardiac function is associated with cognitive impairment and brain imaging features of aging. Cardiac arrhythmias, including atrial fibrillation, are implicated in clinical and subclinical brain injuries. Even in the absence of a clinical diagnosis, subclinical or prodromal substrates of arrhythmias, including an abnormally long or short P‐wave duration (PWD), a measure associated with atrial abnormalities, have been associated with stroke and cognitive decline. However, the extent to which PWD has subclinical influences on overall aging patterns of the brain is not clearly understood. Methods and Results Here, using neuroimaging and ECG data from the UK Biobank, we use a novel regional “brain age” method to identify the brain aging networks associated with abnormal PWD. We find associations between short PWD and accelerated brain aging in the sensorimotor, frontoparietal, ventral attention, and dorsal attention networks, even in the absence of overt cardiac diseases. Conclusions These findings contribute to our understanding of the relationship between PWD and structural brain aging. This work emphasizes the need for continued study designs that consider brain‐based outcomes related to abnormally short PWD.